Qingxue jiedu formulation ameliorated DNFB-induced atopic dermatitis by inhibiting STAT3/MAPK/NF-κB signaling pathways. (24th April 2021) - Xiong, Xin; Huang, Chuanqi; Wang, Fuqian; Dong, Junli; Zhang, Dan; Jiang, Jie; Feng, Yan; Wu, Bin; Xie, Tingting; Cheng, Lu
Abstract: Ethnopharmacological relevance: Qingxue jiedu Formulation (QF) is composed of two classic prescriptions which have been clinically used for more than 5 centuries and appropriately modified through basic theory of traditional Chinese medicine for treating various skin inflammation such as atopic dermatitis (AD), acute dermatitis and rash. Although QF possesses a prominent clinical therapeutic effect, seldom pharmacological studies on its anti-AD activity are conducted. Aim of the study: We used AD mice model to investigate the anti-AD activities of QF, as well as its underlying molecular mechanisms which involved signal transducer and activator of transcription 3 (STAT3), nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways. Materials and methods: 2, 4-dinitrofluorobenzene (DNFB)-induced AD mice were used to collect serum and skin tissues for consequential determination. The levels of various inflammatory factors [interleukin (IL)-12, Interferon (IFN)-γ, tumor necrosis factor (TNF)-α, IL-4, IL-6 and immunoglobulin E (IgE)] were determined by enzyme-linked immunosorbent assay (ELISA). Real-time polymerase chain reaction (RT-PCR) was contributed to detect the effects of relevant inflammatory factors on mRNA. The roles of STAT3, NF-κB and MAPK signaling pathways in AD response were analyzed by Western blotting (WB), and the thickening of mice dorsal skin and inflammatory cell infiltration were observed by hematoxylin and eosin (H&E) staining. Results: QF significantly reduced the skin thickening, inflammatory cell infiltration and other symptoms in AD mice. The levels of IL-12, TNF-α, IL-4, IL-6 and IgE were decreased, while IFN-γ was increased by QF in the ELISA analysis. QF lessened the levels of lL-6 and elevated IFN-γ on the mRNA level. In addition, WB analysis showed QF thoroughly inhibited the activation of NF-κB, STAT3 and phosphorylation of JAK1, JAK2, JAK3, while partially suppressed MAPK signaling pathways. Conclusions: QF inhibited the activations of STAT3, MAPK and NF-κB signaling pathways and possessed a significant therapeutic effect on AD. Therefore, QF deserves our continuous attention and research as a prominent medicine for AD. Graphical abstract: Image 1 Highlights: Mechanism analysis of Traditional Chinese medicine formulation. Analysis of Chinese medicine in the treatment of atopic dermatitis. Evaluation of STAT3, MAPK and NF-κB signaling pathways in Qingxue jiedu Formulation (QF) for AD therapy.